The impact of political, financial, and economic risks on energy transition: the role of natural resource rents - Qiang Wang; Xueting Li; Rongrong Li (Humanities & Social Sciences Communications)
Abstract The global emphasis on energy transition arises from the recognition of fossil fuel reliance exacerbating environmental degradation. The transition to cleaner, renewable energy sources stands central in mitigating climate change and promoting sustainability. This paper explores the influence of country risks, particularly political, financial, and economic, on energy transition while considering the role of natural resource rents. Using data spanning 88 countries from 2006 to 2020, categorized by income levels, the analysis reveals distinct patterns. Low political and financial risks exhibit a negative correlation with energy transition, while low economic risks display a positive association. The study identifies threshold effects: higher resource rents worsen the negative impact of low political and financial risks and weaken the positive effects of low economic risk on energy transition. These relationships differ among countries with different income levels. These insights highlight the nuanced interplay between country risks, natural resource rents, and the trajectory of the energy transition, crucial for steering societies toward sustainable development pathways.